Working with statistics : an introduction to quantitative methods for social scientists - Reid, Stuart. (Polity Press, 1987)
An argument for statistics. Methodological considerations. The vocabulary of social research. Odering the data. Summarizing the data. Taking a sample. Working with two variables. Working with three or more variables.